PERLINDUNGAN HUKUM TERHADAP HAK PASIEN LANJUT USIA DI PUSKESMAS X KOTA KEDIRI - Indah susilowati; Ryan Nur Firmansyah (Asosiasi Perguruan Tinggi Rekam Medis dan Informasi Kesehatan Indonesia- APTIRMIKI, 2018)
Puskesmas X is one of the first health facility in Kediri Town that serves elderly patient, in registration, elderly patient has right of service priority and clear information. The goal of the research is to see the availability of information that support the service and review it from medical law’s aspect. Descriptive design, 50 samples of elderly that come to elderly polyclinic with incidental sampling technique. Data collection uses checklist sustained by questionnaire and interview. The result of the research shows that there is no rule and SOP about elderly patient service yet, but the information in registration is already good, there is an information of opening hour, there is an information of what requirement should be brought, information about service tariffs, there is a loudspeaker to summon elderly patient queue, there is no special registration place, but there is a special queue number and a special service room to accelerate the elderly service, there is no information of doctor’s name that treat yet and there is no information about other health facility that cooperate as reference place, but registration officer is already good at serving elderly by communicating with easy-to-understand language and friendly. The conclusion of this research is basic policy and SOP that protect elderly patient has not available yet, but patient rights to get information and services in registration is available well.